2021
DOI: 10.1108/jgm-03-2021-0029
|View full text |Cite
|
Sign up to set email alerts
|

Radical changes in the lives of international professional women with children: from airports to home offices

Abstract: PurposeThe purpose of the paper is to discover the impact of restrictions connected with the coronavirus disease (COVID-19) pandemic on the work and life of international professional women with children.Design/methodology/approachA qualitative, explorative research was conducted with 12 international professional women, who were professional women with children under 12; semi-structured online interviews were used.FindingsThe radical decrease in international travel combined with an increase in online work an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…There is a consensus that the pandemic has caused unprecedented changes in mobility habits in many countries. Growing trends in travel by private cars (Campisi et al 2020 ), e-commerce and online shopping and work (Villa and Monzon, 2021 ; Primecz 2021 ), less desire for public transportation (Tirachini & Cats 2020 ), and connecting and meeting online (Nabity-Grover et al 2020 ) have been observed in many countries. Advances in smart solutions and technologies have played a major role in creating these changes (Nabity-Grover et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is a consensus that the pandemic has caused unprecedented changes in mobility habits in many countries. Growing trends in travel by private cars (Campisi et al 2020 ), e-commerce and online shopping and work (Villa and Monzon, 2021 ; Primecz 2021 ), less desire for public transportation (Tirachini & Cats 2020 ), and connecting and meeting online (Nabity-Grover et al 2020 ) have been observed in many countries. Advances in smart solutions and technologies have played a major role in creating these changes (Nabity-Grover et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ozcelik and Sevinc (2022) states that being lonely at home was also identified as a negative aspect for work from home concept. Primecz (2022) states that online meetings provided an excellent tool to share documents and work on projects with several people with reduced travelling time and higher productivity. Wong et al (2021) argued that that on -line working styles are not suitable for hands -on work and only limited days of the year can work be done at house for operations such as writing reports of field visits.…”
Section: Resultsmentioning
confidence: 99%
“…The focus of this paper is specifically on SIEs employed on local, contracts in their host countries, where the initiative for the move was taken by the individual (Andresen et al, 2012). Thus, there is no organizational relocation support or onboarding measures as would be the case with a traditional company-transferred expatriate (Caligiuri and Lazarova, 2002;Caligiuri et al, 2020;Philips, 2020;Primecz, 2021;Shao and Al Ariss, 2020).…”
Section: Defining Siesmentioning
confidence: 99%
“…It is important for organizations to become aware of the impact of external crises on the individual's micro-environment: For women, the need to care and protect their families may take precedence during times of crisis (Primecz, 2021). The focus of the individual shifts to the CDI 28,4 own inner circle and work intensification over the duration of the crisis can add to the load that is already on the shoulders of this vulnerable group (Stroud Stasel, 2023).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation